Android-based augmented reality for writing learning for university students: A case study of Indonesian students’ writing literacy problems - Fujiastuti, Ariesty; Wirawati, Denik (Association for Scientific Computing Electrical and Engineering(ASCEE), 2025)
This study explores the development and effectiveness of Android-based Augmented Reality (AR) learning media to enhance university students' writing skills in Indonesian language courses. The background stems from challenges observed in writing classes, where reliance on static PowerPoint presentations and lack of interactive media contributed to low student engagement and limited writing outcomes. Utilizing the ADDIE model, this developmental research involved stages of analysis, design, development, implementation, and evaluation. Media content was designed using Macromedia Flash integrated into Android-based AR, focusing on accessibility, interactivity, and the Technological Pedagogical Content Knowledge (TPACK) framework. Validation from material and media experts indicated high feasibility (scores of 3.87 and 3.77, respectively), while student response yielded an Aiken's V index of 0.95–1, categorized as excellent. An experimental test involving control and treatment groups demonstrated significant improvement in writing skills (p-value 0.05). The results suggest that Android-based AR media effectively supports meaningful and engaging writing instruction, addresses students’ literacy gaps, and aligns with 21st-century learning needs. This study contributes to educational technology and writing pedagogy by offering an innovative solution to writing literacy challenges in higher education.